Decision Support System for Evaluation of Java Learning in Elementary School (SD) Using Cummulative Voting Method - Fajrul Islam; Rani Purbaningtyas; Syariful Alim; Rifki Fahrial Zainal (Fakultas Teknik Universitas Bhayangkara, 2020)
Javanese is a language used by Javanese ethnic groups in Central Java and East Java, learning Javanese should be done by Javanese people to carry on the language of ancestral heritage so that Javanese language will not disappear in the future. To support effective and flexible learning tools, learning evaluations are needed so that teachers know the extent of students' understanding of Javanese language, the purpose of this research is to make it easier for students to learn Javanese in the learning process and in order to make teachers evaluate. From these problems led to the idea to create a web-based application in which it can carry out an accurate assessment process using the Cumulative Votting method with a Likert Scale. The programming language uses PHP and the database uses MySQL. From the test results using a Likert Scale manual values tested at 3 places found the results, namely, Gresikan Village Elementary School students get an interval value of 67.5% with a